Changes in serum creatine kinase, leg muscle tightness, and delayed onset muscle soreness after a full marathon race - Tojima, M.; Noma, K.; Torii, S. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: Muscle tightness (MT) is believed to be an important cause of injury for runners. This study evaluated the change of serum creatine kinase (CK), MT in the leg muscles, and delayed onset muscle soreness after running.